Subcutaneous Immunization with Fusion Protein DnaJ-ΔA146Ply without Additional Adjuvants Induces both Humoral and Cellular Immunity against Pneumococcal Infection Partially Depending on TLR4 - Su, Yufeng; Li, Dagen; Xing, Yan; Wang, Hong; Wang, Jian; Yuan, Jun; Wang, Xiaofang; Cui, Fang; Yin, Yibing; Zhang, Xuemei (Frontiers in Immunology, 2017)
Subunit vaccines that are poorly immunogenic are often combined with adjuvants for immunization. Our previous research identified a pneumolysin variant (ΔA146Ply), a Toll-like receptor 4 agonist, that was an effective adjuvant in the protection of fusion protein DnaJ-ΔA146Ply against mucosal Streptococcus pneumoniae infections. For pneumococcal vaccines, World Health Organization recommend injection as a regular vaccination approach. Subcutaneous immunization is a common and effective method of injection, so we explored the immunity mechanism of subcutaneous immunization with DnaJ-ΔA146Ply. We found that mice immunized subcutaneously with fusion proteins ΔA146Ply-DnaJ and DnaJ-ΔA146Ply produced a higher anti-DnaJ IgG titer than when DnaJ alone was administered. DnaJ-ΔA146Ply induced both B-cell and T-cell-dependent protection against both colonization and lethal pneumococcal infections. Levels of IFN-γ, IL-4, and IL-17A were also elevated in DnaJ-ΔA146Ply immunized mice. However, all these effects were negated in TLR4−/− mice compared to WT mice immunized with DnaJ-ΔA146Ply. B-cell-deficient μMT mice, nude mice, IFN-γ−/−, and IL-4−/− mice immunized with DnaJ-ΔA146Ply could not resist infection with pneumococci. IL-17A−/− and TLR4−/− mice did not benefit from DnaJ-ΔPly immunization in colonization experiments although their survival was not impaired compared with WT mice. Collectively, our data indicated that ΔA146Ply can be a potential subcutaneous adjuvant, and the DnaJ-ΔA146Ply fusion protein induces both humoral and cellular immune response to resist S. pneumoniae infection. The protective effect of colonization also depends on TLR4.